2022
DOI: 10.1111/j.1755-3768.2022.0075
|View full text |Cite
|
Sign up to set email alerts
|

chronic glaucoma in rats induced by single injection of fibronectin‐loaded PLGA microspheres

Abstract: Purpose: To generate a model of chronic glaucoma in rats, by means of a single injection that simulates the pathology that occurs in humans. Methods: A total of 47 Long‐Evans rats of both sexes were used; 30 rats received an intracameral injection of a suspension of fibronectin‐loaded poly‐lactic‐glycolic acid microspheres into the right eye, and the other 17 served as controls. They were followed up for 24 weeks, evaluating intraocular pressure (IOP) with a rebound tonometer, neuro‐retinal structure by optica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Figure 2. In vivo methodology on the animals was performed as in our previous works [35]. For details, please see Supplementary methods 2.…”
Section: E)mentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2. In vivo methodology on the animals was performed as in our previous works [35]. For details, please see Supplementary methods 2.…”
Section: E)mentioning
confidence: 99%
“…To avoid frequent interventions new glaucoma animal models based on the intraocular pressure elevation, and subsequently, retinal glaucomatous damage, by injection of loaded and non-loaded biodegradable microparticles in the anterior chamber of the eye have been proposed in the last years [31][32][33][34]. In the present work, one of the mentioned models has been selected for neuroprotection activity studies, where glaucomatous damage in the retina was observed over six months after a single intracameral injection of fibronectin (FN) loaded PLGA microspheres, mimicking the progression of the disease in humans [35]. The main advantage of this animal model is that the chronic retinal damage is created by a single injection of FN-loaded particles in the anterior chamber, with no damage of any other ocular structure, furthermore, this model allows to test intravitreal drug delivery systems for long periods.…”
Section: Introductionmentioning
confidence: 99%